A valorização das “taipas de pedras” como estratégia para a conservação da paisagem dos Campos de Altitude em São Francisco de Paula/ RS, Brasil - Ismael Jesus Klein; Márcia dos Santos Ramos Berreta (Confins)
The taipas are stone walls found in the region of Campos de Cima da Serra in the state of Rio Grande do Sul, Brazil. Associated with the tropeirismo, an important commercial route of the Brazilian colonial period, they have as main characteristic the fact that they had been built without the use of any type of mortar, but only with embedded stones, Which is why they’re also known as the dry stone wall. The objectives of this research are: a) to map the taipas in the territory of the municipality of São Francisco de Paula in order to spatially highlight the marks in the landscape, characterizing them by their uses; b) to evaluate the relationship of the preservation of the taipas as a cultural heritage with the conservation of the Campos de Altitude of the Atlantic Forest, constituting the same landscape of the Campos de Cima da Serra. This study was based on two important steps. The first refers to the Bibliographic Research and the information collected from local actors. In the second, the taipas were mapped through visualization in Google Earth images, manually vectorized and the map elaborated in Software Qgis. Were mapped 81 km from Taipas in the territory of the municipality and can be seen that these are cultural heritage established by law and also important marks in the landscape. This importance is justified, because they refer to the history of the municipality and the beginning of the regional colonization. In summary, landscape studies can contribute to the elaboration of public policies aimed at the conservation of both the taipas and the Campos de Altitude, as they are elements of the same landscape and together constitute the municipal cultural heritage.